Bird in the wire: creativity, resistance, networked citizenships. Issue 1 (2nd January 2017) - Cleeve, Sam
ABSTRACT: This paper contemplates the extent to which online music-making and sharing practices can be understood as acts of creative citizenship. While the digital is often lauded as a mechanism by which citizens may engage creatively with local or national communities, this paper contends that it may equally represent a means for dis engagement with those groups, by instead facilitating participation in the transnational, diasporic communities that have long prospered on the Internet. Possible motivations for this are multifarious and context-dependent, but often signify an act of resistance: against artistic and commercial institutions, against creatively oppressive states, against the cultural isolation of an immediate environment. This paper holds that this type of digitally mediated creative engagement—that which arises as a specific reaction to a perceived inadequacy in one's civic life—might be best understood through the lens of creative citizenship. In order to assess the relationship between online creative communities and their offline counterparts, it employs Wellman and Castells' notion of 'networked individualism', and contextualizes its ideas by referring to recent studies in online amateur music-making in Iran, where the digital is often regarded as a way of circumnavigating the creative oppression of the state.